RGD peptide on Dendrimer surfaces Affects Mesenchymal Stem Cells Adhesion - Vida-Pol, Yolanda; Molina, Noemi; Collado-Martín, Daniel; Nájera-Albendín, Francisco; Lagunas, Anna; Claros-Gil, Silvia; Becerra-Ratia, José; Andrades-Gómez, José Antonio; Pérez-de-Inestrosa-Villatoro, Ezequiel (My University, 2016)
Mesenchymal stem cells (MSCs) are promising candidates for a range of tissue regeneration applications. Adequate scaffolds are necessary for their application in vivo, where interactions between cells and the surface material are critical. Arginine-glycine-aspartic acid tripeptides (RGD) were conjugated to Polyamidoamine (PAMAM) dendrimers and used to pre-treat test surfaces. We demonstrate that dendrimer-presented tripeptides efficiently increase surface cell adhesion to MSCs, and that their effectiveness is related to how they are presented by the dendrimer to the cell. Cell adhesion process is governed by the nanoscale arrangement of the extracellular matrix (ECM), being more affected from local than from global concentration of cell adhesive ligands. Dendrimers grafted on surfaces showed the benefits of the local increase in concentration provided by the dendritic configuration, in many cell-based studies. Dendrimer nanopatterning is applied to address RGD density effects on cell adhesion, where cell experiments showed a clear correlation with dendrimer surface layout. Therefore, dendrimer nanopatterning is presented as a suitable and controlled approach to address the effect of local ligand density in cell response.[
Keywords: Regeneración (Biología); RGD; Dendrimers